Experiments in nuclear physics using inexpensive instruments - Saminan, Saminan; Silviana, Fitria; prayogi, soni (Universitas Sebelas Maret, 2023)
The scarcity of experimental activities is one of the challenges of teaching current physics. This study resolves these issues and suggests three nuclear physics experiments using a low-cost ion chamber, whose construction is explained: the measurement of 222Rn progeny collected from the indoor air; the measurement of the range of alpha particles emitted by the 232Th progeny, present in lantern mantles and in thoriated welding rods, as well as by the air filter containing 222Rn progeny; and the measurement of 220Rn half-life collected from In this study, the experimental methods and anticipated findings are presented, showing that the experiments could help nuclear physics curricula. These procedures may provide broad access to either academic laboratories in high schools or colleges and the equipment may be used to create novel nuclear physics teaching strategies